Contribution of the Kharkiv parovozobudivnyj plant to development of parovozobudivnyj industry on territory of Ukraine - O. L. Sorochynska (History of science and technology, 2013)
Briefly shows the contribution of the Kharkov Locomotive Works in the development of the locomotive industry in Ukraine. The main types of locomotives, which were built at the Kharkov Locomotive Works. Definitely the importance of nucleation locomotive industry in Ukraine.